USING ALTERNATIVE ENERGIES IN INTERNAL COMBUSTION ENGINES - Abutolib Sobirjonov; Vaxob Meliev; Ilxomjon Usmanov (Web of Journals Publishing, 2024)
This article presents the state-of-the-art research on the hydrogen fueled internal combustion engine. First, the fundamentals of the hydrogen engine are described by studying the engine-specific properties of hydrogen, and then the existing literature is reviewed.
Keywords: Internal combustion engine, hydrogen, emissions, alternative fuel 1.